P4_7 It's a Man Eat Man World - Graham, Holly; Sainty, William; Kneeshaw, Sam; Howard-Clark, Simon (Physics Special Topics, 2017)
In this paper we calculated how long the human race would last if it resorted to cannibalism and only cannibalism. We took into account how many calories a human is comprised of, using the value for an average human male, and that each human will consume exactly 2500 kcal a day in accordance with the recommended calorie intake for men. Using a decay model, we found that 1 person would be left alive after 1149 days.